4-Formylazetidin-2-one as a useful building block for the formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine - Kale, Ajaykumar S.; Sakle, Prathmesh S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
Stereoselective formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine is described starting from an enantiopure formyl-substituted P-lactam. Grignard reaction of the N-Boc-protected-beta-lactam carbonyl group, followed by further transformations, provides a common intermediate for xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine.
Keywords: azetidin-2-one; beta-lactam; Grignard reaction; Phytosphingosine; Sphingosine